Leiautes Dinâmicos para Documentos Multimídia Baseados em Templates - Amorim, Glauco Fiorott; Muchaluat-Saade, Débora Christina (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Template-based languages can be used for arranging interface components in a layout model, like a grid. Declarative multimedia authoring languages, such as NCL (Nested Context Language), may use those templates for decreasing the authoring effort while specifying a presentation spatial layout. Although layout models are helpful for specifying presentation characteristics for media items, they usually do not consider the case where changes may happen at runtime. Moreover, presentations may lose tidiness when displayed on a device different then the one it was designed for or due to the viewer context or even due to viewer interaction. This thesis proposes STyLe, a template language for dynamic spatial layout. STyLe is a constraint-based template language for providing dynamic and adaptive spatial layouts for hypermedia documents. It also presents a framework capable of interpreting this language and performing the necessary changes in order to dynamically update NCL media object presentation characteristics at runtime.